Determining the impact of on-line practicum facilitation for in-service teachers - Frey, Timothy (My University, 2009)
This study investigated the impact of a project-based graduate practicum experience that was facilitated on-line. The study investigated the affects of the on-line practicum experience by: (1) using quantitative data to assess the learning and professional growth of the practicum participants in comparison to a group of teachers that did not participate in the practicum experience, and (2) identifying the qualitative components of the practicum experience that facilitated successful completion and implementation of best practice teaching skills of the practicum participants. Findings indicated that teachers did change instructional practices as a result of the practicum experience, and identified three critical components of the on-line practicum: 1) use of meaningful learning activities, 2) collaborative learning communities, 3) structure of the practicum project. Effective use of these components can facilitate significant professional growth for in-service teachers engaged in on-line practicum experiences.
Keywords: Teachers; Distance education; Educational technology; Professional development; Teaching methods; Practica